Appraising managers as managers - Koontz, Harold (United state of America McGraw-Hill, 1971)
This book emphasizes both appraisal against objectives and appraisal of managers as managers. The conclusion suggested the need for a based participation in and experience with appraisal in both business and government operations.
Includes bibliographical reference
mf 23/01/2019
Loans
Keywords: Executives; New York